The Effect of Trust Information Quality and Discount on Cosmetic Purchasing Decisions through Online Media - Adisyah Nurul Budiasih; Syamsu Nujum; Mapparenta Mapparenta (Journal La Bisecoman, 2024)
The Effect of Trust Information Quality and Discount on Cosmetic Purchasing Decisions in E-commerce Platforms (Study Case: Members of UKM Entrepreneurial UMI (supervised by Hj. Syamsu Nujum and H. Mapparenta). This research aimed to rigorously examine and investigate: (1) the impact of trust on purchase decisions on cosmetic products via online media by the members of UKM Entrepreneurial UMI; (2) the impact of information quality on the purchase decisions; and (3) the effect of discounts on the purchase decisions. Employing primary data, 174 members of UKM Entrepreneurship UMI were taken as a sample, and the data was collected through a survey conducted from November to December 2023. The data analysis used was the multiple linear regression analysis method assisted by SPSS 24. The results of this research reported that: (1) trust demonstrated a positive and significant effect on purchase decisions; (2) information quality illustrated a positive and significant effect on purchase decisions; (3) discounts denoted a positive and significant effect on purchase decisions.